Формирование профессиональных навыков преподавателя необходимых для успешной педагогической деятельности - Болдырев, Кирилл Владимирович (Institutul Internațional de Management Imi-Nova, 2018)
Modern requirements to the development and professional criteria of the teacher are formed according to the latest trends in pedagogy and development of society in conditions of total globalization. Their main positions are the uniqueness of requirements, the improvement of the standards of the educational system, the transformation of previously acquired experience and knowledge into actual teaching methods.
Keywords: педагоги; требования; развитие; профессиональная компетентность; психологи; педагогика; образовательная система